Detecting ionospheric precursors of a deep earthquake (378.8 km) on 7 july 2013, m w=7.2, in papua new guinea under a geomagnetic storm: two-dimensional principal component analysis (2013)
Two-dimensional ionospheric total electron content (TEC) data were collected during the time period from 00:00 on 2 July to 12:00 UT on 08 July 2013. This period spanned 5 days before to 1 day after a deep earthquake (378.8 km) in Papua New Guinea at 18:35:30 on 7 July 2013 UT (Mw=7.2). Data were examined by two-dimensional principal component analysis (2DPCA) to detect TEC precursors related to the earthquake because TEC precursors have usually appeared in earlier time periods (Liu et al. 2006). A TEC precursor was highly localized around the epicenter on 6 July for 5 minutes, from 06:00 to 06:05. Ionizing radiation from radon gas release could possibly have caused the anomalous TEC fluctuation through, for example, a density variance. The plasma might have experienced large damping to cause short-term TEC fluctuations, and the gas released in a small amount in a short time period. 2DPCA can also identify short-term TEC fluctuations, but this fluctuation lasted for a considerable length of time. Other background TEC anomalies caused by the geomagnetic storm, small earthquakes and non-earthquake activities, e.g., equatorial ionization anomaly (EIA), resulted in small principal eigenvalues. Therefore, the detection of TEC precursors through large eigenvalues was not due to these background TEC anomalies. ResumenDatos del contenido total de electrones ionosféricos en dos dimensiones (TEC) fueron medidos durante el período del 2 de julio de 2013, a las 0:00:00 horas GMT., hasta las 12:00 GMT. del 8 de julio. En este lapso se abarcan cinco días antes y un día después de un terremoto profundo (378,8 kilómetros) en Papúa Nueva Guinea, que se presentó a las 18:35:30 del 7 de julio (M w =7.2). Los datos fueron examina- dos a través de los componentes principales en dos dimensiones (2DPCA) para detectar los precursores TEC relacionados al terremoto (Liu et al. 2006). Un precursor de los TEC fue localizado alrededor del epicentro el 6 de julio durante 5 minutos, desde las 06:00 a las 06:05. La radiación ionizada por la liberación de radón podría haber causado la fluctuación anómala de los TEC a través de, por ejemplo, una variación de densidad. El plasma podría haber experimentado una fuerte humectación lo que cau- saría fluctuaciones cortas de los TEC y la liberación de gas en pequeñas cantidades en poco tiempo. A través de los 2DPCA también se pueden identificar fluctuaciones cortas de los TEC, pero estas últimas duraron por un tiempo considerable. Otras anomalías en el entorno de los TEC causadas por tormentas geomagnéticas, pequeños terremotos y actividades no sísmicas, por ejemplo la anomalía ecuatorial de ionización (EIA, en inglés), resultaron en pequeños autovalores principales. Por lo tanto, la detección de precursores TEC a través de grandes valores propios no se debe al entorno de estas anomalías en los TEC.